THE ROLE OF PHARMACISTS IN PATIENT CARE AND MEDICATION MANAGEMENT. - Abdullah Hamed Alonazi; Faris Abdullah Khalaf Almutairi; Fahad Abdullah Ajab Alshkarah; Meshari Mohammad Alotaibi; Mohammed Abdulaziz Mohammed Alshibreen; Ibrahim Abdullah Mesfer Aldawsari (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Pharmacists play a crucial role in patient care and medication management. They are highly trained healthcare professionals who work closely with patients, physicians, and other healthcare providers to ensure the safe and effective use of medications. This essay explores the various ways in which pharmacists contribute to patient care and medication management, including medication therapy management, medication reconciliation, patient counseling, and collaboration with healthcare teams. The essay also highlights the importance of pharmacists in promoting medication adherence, preventing medication errors, and improving patient outcomes. Overall, pharmacists serve as essential members of the healthcare team, playing a key role in optimizing patient care and medication outcomes.